2005
DOI: 10.2220/biomedres.26.69
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal regeneration in intrabony defects after application of enamel matrix proteins with guided tissue regeneration: An experimental study in dogs

Abstract: The aim of this study was to evaluate the effects of enamel matrix proteins (EMP)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…It has been suggested that GTR treatment promotes this mechanism by blocking contact between epithelial and gingival connective tissues and the exposed root surface 6,18) . Taken together with those of earlier studies 19) , the results of the present study suggest the presence of progenitor cells from adjacent, undisturbed and healthy PDL or bone marrow.…”
Section: Discussionsupporting
confidence: 90%
“…It has been suggested that GTR treatment promotes this mechanism by blocking contact between epithelial and gingival connective tissues and the exposed root surface 6,18) . Taken together with those of earlier studies 19) , the results of the present study suggest the presence of progenitor cells from adjacent, undisturbed and healthy PDL or bone marrow.…”
Section: Discussionsupporting
confidence: 90%
“…However, no statistically significant differences in any of the investigated parameters were observed between the test and control groups; therefore, the investigators concluded that the combination of Er:YAG laser and enamel matrix protein derivative did not improve the clinical outcome of surgical therapy. As reported previously, the use of enamel matrix protein derivative itself might improve the clinical outcome of periodontal surgery 43‐48 …”
Section: Discussionmentioning
confidence: 74%
“…Additionally, one tooth transplanted with EMD showed root resorption after drying, while resorption was noted in all teeth transplanted without EMD. EMD was detected as early as day 2 on all the teeth transplanted with EMD and was still demonstrated after 4 weeks 62. However, this effect was limited to the first 4 weeks following surgery, indicating that the main effect of EMD is at the early stage of periodontal wound healing.…”
Section: Controlled Histologic Studies In Animalsmentioning
confidence: 94%